A retrospective analytical study of caesarean section in intrauterine foetal death cases in a rural medical college - Patra, Kajal; Chattopadhyay, Shibram; Samanta, Poulami; Mondal, Chandrakanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrauterine fetal death(IUFD) is an unhappy reality, a lamentable incidence for both the family and the caregiver. It is an important indicator of both maternal and perinatal health in a population. The study of fetal death is crucial in promoting actions for maternal and child health. Aim of this study was to determine the incidence, indications and maternal morbidity and maternal mortality associated with caesarean section in patients with IUFD and to establish the place of caesarean section in present day scenario. Methods: The study was a retrospective analysis of all caesarean section carried out in a case of IUFD in last 5 years (2013-2017). The indications, incidence, maternal morbidity, mortality was studied well in this time period in a rural medical college of West Bengal. Results: Total 108425 deliveries occurred in the hospital in last 5 years, out of which 31800 were caesarean section. 56 cases were done in case of diagnosed IUFD. There was 2489 number of IUFDs in the given period. The incidence of IUFD was 22.96 per 1000 deliveries. Induction was done in 2489 cases; 56 cases underwent caesarean section (2.25%) and rest was delivered vaginally. Conclusions: Early diagnosis, early referral and proper antenatal checkup can reduce the chances of IUFD and number of caesarean deliveries in IUFD. The role of cesarean deliveries in previous caesarean deliveries having IUFDs has been emphasized.